Micro/Nano‐Pores and Anti‐Fingerprint Coating by Vacancy‐Capture and Interface Intelligent Control - Yimin Luo; Boran Hao; Jingbo Li; ZhiPeng Liu; Yujie Yang; Litao Chen; Shuaikang Liu; Zhuangzhu Luo (Advanced Materials Interfaces, 2023)
Abstract In this work, a simple anti‐fingerprint strategy (reduced ≈40–60%) to rearrange fingerprint droplets by patterned micro/nano‐pore/spoons texture, air cushion and low surface energy is reported. Superior to previous precise and complex preparation methods, the micro/nano‐texture are fabricated through conventional process of spray and dip. The pore and spoon can be freely switched by changing the process. The number (N) and size (r) of pores and spoons are controlled intelligently by solvent volatilization and interfacial tension (γFP/PU−H2O and γFP/PU − Solvent), the key for pore/spoon's forming and expanding. A physical model of interface intelligent controlling the micro/nano‐pore/spoon surface texture induced by “Vacancy‐Capture” is proposed. The description is being reported, for the first time, to the knowledge, expecting to make it possible to prepare anti‐fingerprint engineering materials with newly potential industrial applications on optical device for large‐scale in the future.